The Cleanliness For A Healthy Life : A Preventive Remedy In Tibbin Nabawi - Fadzli, Adam; Fauzi, Yusoh; Muhammad Hedayatul, Islam; Rohaizan, Baru (2019)
Tibbin Nabawi (Prophetic Medicine) is a divine remedy for a healthy life and family. Popular herbal and Ayurveda medicine promote a symbolic narration “prevention is better than cure”. Likewise, Tibbin Nabawi is divinely instructed and applied in the traditions of the Prophet Muhammad (s.a.w.) which compassionate both prevention and cure for the human body and soul. The modern medical science, however, tremendously grabbed some ideas and treatments that are very much relevant to the natural and divine practice of the Prophet. Tibbin Nabawi might have accredited one of the best remedy and autophagy to prevent and gradually cure fatal diseases. This study aims at investigating the relevance to the concept of divine remedy and the practice of the Prophet called “tibbun nabawi” with special reference to the concept of taharah or cleanliness. This study also substances to explore the following; i) wudhu (ablution), and ii) siwaak (tooth-brush). This research first examines tibbin nabawi from main sources - the Qur’an and Sunnah and the interpretation and approach of Muslim scholars to formulate a balanced and healthy life. This study finds the concept of tibbin nabawi is an important means that complements modern medical treatment. Furthermore, tibbin nabawi is a leading physical and spiritual paradigm to fight the toxic disease of the human body as well as to reshape the modern medical science which corresponds to the divine practice of the Prophetic traditions. This study concludes tibbin nabawi has the potential not only in promoting a ‘balanced and healthy lifestyle’ as championed by the Prophet of Islam but also to improve a moderate, healthy and peaceful life which is in favor of the well-being of the human body and soul.